Biomolecular Evidence of Early Human Occupation of a High-Altitude Site in Western Central Asia During the Holocene - Schroeter, Natalie; Lauterbach, Stefan; Stebich, Martina; Kalanke, Julia; Mingram, Jens; Yildiz, Caglar; Schouten, Stefan; Gleixner, Gerd (Frontiers in Earth Science, 2020)
Reconstructions of early human occupation of high-altitude sites in Central Asia and possible migration routes during the Holocene are limited due to restricted archeological sample material. Consequently, there is a growing interest in alternative approaches to investigate past anthropogenic activity in this area. In this study, fecal biomarkers preserved in lake sediments from Lake Chatyr Kol (Tian Shan, Kyrgyzstan) were analyzed to reconstruct the local presence of humans and pastoral animals in this low-human-impact area in the past. Spanning the last ∼11,700 years, this high-altitude site (∼3,500 m above sea level) provides a continuous record of human occupancy in Western Central Asia. An early increase of human presence in the area during the mid-Holocene is marked by a sharp peak of the human fecal sterol coprostanol and its epimer epicoprostanol in the sediments. An associated increase in 5β-stigmastanol, a fecal biomarker deriving from herbivores indicates a human occupancy that most probably largely depended upon livestock. However, sterol profiles show that grazing animals had already occupied the catchment area of Lake Chatyr Kol before and also after a significant presence of humans. The biomarker evidence in this study demonstrates an early presence of humans in a high-altitude site in Central Asia at ∼5,900–4,000 a BP. Dry environmental conditions during this period likely made high altitude regions more accessible. Moreover, our results help to understand human migration in Western Central Asia during the early and mid-Holocene as part of a prehistoric Silk Road territory.